THE EFFECT OF FIRM SIZE AND DER ON FINANCIAL PERFORMANCE IN BUMN COMPANIES - Dwiningsih, Sri; Ratnasari, Ike; Putri Handita, Annisa (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This research was conducted to analyze financial performance (ROE) with analytical tools using Firm Size and Debt to Equity Ratio. The population of this study is all state-owned companies in 2018-2021 on the Indonesia Stock Exchange with the number of samples taken according to the researcher's criteria of 10 state-owned companies. The data collection technique used is the documentation method. Data analysis techniques used normality, multicollinearity, heteroscedasticity, multiple regression analysis, hypothesis testing t-test and F-test, Coefficient of Determination (R2). The results of the study partially show that the Firm Size (FS) variable has a positive and significant effect on financial performance (ROE) in BUMN companies, the Debt to Equity (DER) variable has no significant effect on financial performance (ROE) in BUMN companies, simultaneously the Firm Size variable ( FS)